2021
DOI: 10.7717/peerj.11918
|View full text |Cite
|
Sign up to set email alerts
|

Wheat litter and feed with aluminosilicates for improved growth and meat quality in broiler chickens

Abstract: Background Natural minerals have many beneficial properties in poultry production, taking into account production as well as hygiene, health, safety, and quality of broiler meat. The aim of the study was to evaluate the effect of aluminosilicates in feed and litter on the growth performance and meat quality in chickens. Aluminosilicates, including halloysite and zeolite, could be a good alternative for synthetics, as a good solution for the environment in line with the current trends. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Raj et al 26 showed that the addition of a mycotoxin-reducing substance with modified zeolite in feed for broiler chickens at the level of 1 g/kg and 2 g/kg improved the feed conversion ratio (FCR). In the study by Banaszak et al 27 , broiler chickens were reared with the addition of aluminosilicates in the feed at the level of 0.5–2% (25% halloysite and 75% zeolite) in the feed and 0.950 kg/m 2 of wheat litter (1:1 halloysite and zeolite) were characterized by higher BWG without affecting FI and FCR. Using zeolite and halloysite 0.5–2% in the feed, with the simultaneous addition of aluminosilicates to the rye litter at 800 g/m 2 (with different proportions), resulted in higher BW and BWG of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raj et al 26 showed that the addition of a mycotoxin-reducing substance with modified zeolite in feed for broiler chickens at the level of 1 g/kg and 2 g/kg improved the feed conversion ratio (FCR). In the study by Banaszak et al 27 , broiler chickens were reared with the addition of aluminosilicates in the feed at the level of 0.5–2% (25% halloysite and 75% zeolite) in the feed and 0.950 kg/m 2 of wheat litter (1:1 halloysite and zeolite) were characterized by higher BWG without affecting FI and FCR. Using zeolite and halloysite 0.5–2% in the feed, with the simultaneous addition of aluminosilicates to the rye litter at 800 g/m 2 (with different proportions), resulted in higher BW and BWG of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…Raj et al 26 showed that the addition of a mycotoxin-reducing substance with modified zeolite in feed for broiler chickens at the level of 1 g/kg and 2 g/kg improved the feed conversion ratio (FCR). In the study by Banaszak et al 27 , broiler chickens were reared with the addition of aluminosilicates in the feed at the level of Table 3. Relative weight and length of individual sections of the digestive system of broiler chickens.…”
Section: Discussionmentioning
confidence: 99%
“…During the gutting process, the edible offals were collected (heart, liver, gizzard). The prepared carcasses were chilled in a refrigerator (Hendi, Poznan, Poland) at 4°C for 24 h ( Banaszak et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The measurement was repeated 24 h after weighing the carcasses (pH 24hours ). After dissection, the right and left pectoral and leg muscles were collected for further analysis ( Banaszak et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The device was calibrated with buffers of pH = 4.00, 6.00, and 9.00. The measurement was repeated after 24 h [ 22 ]. The carcasses were weighed (Radwag, Radom, Poland) and dissected.…”
Section: Methodsmentioning
confidence: 99%